The Effect of Self-Efficacy and Sense 0f Community on Higher Order Thinking Ability of Students Schoology-Assisted Learning - Arfiyan Charles Manihuruk; Nengah Maharta; wayan Suana (Universitas Lampung, 2020)
This study aims to determine the effect of self-efficacy (SE) and sense of community (SC) on the ability to think of high-level students in learning Newton's law material about gravity aided by Schoology. The research design used was Non-Equivalent Pretest Posttest Control Group Design. Data were tested by single linear regression and multiple linear regression tests. Based on the results of the Higher Order Thinking Skills (HOTS) single linear regression test with SE correlation coefficient of 0.035 so that both do not have a significant relationship. HOTS with SC correlation coefficient of 0.013 so that both do not have a significant relationship. Multiple regression test The results of the regression analysis above shows the price coefficient of determination equal to 0.003. This value means that 0.3% change in the variable HOTS can be determined by SE and SC while 99.7% is explained by other variables not examined in this study. This shows that there is no positive and insignificant relationship between Blended learning assisted by Schoology to higher level thinking skills seen from students SE and SC.Keywords: Blended Learning, Higher Order Thinking Skills (HOTS), Self-Efficacy (SE), Sense of Community (SC)DOI : http://dx.doi.org/10.23960/jpvti.v2.i1.202001